Diversity and Distribution of Prokaryotes within a Shallow-Water Pockmark Field - Giovannelli, Donato; d'Errico, Giuseppe; Fiorentino, Federica; Fattorini, Daniele; Regoli, Francesco; Angeletti, Lorenzo; Bakran-Petricioli, Tatjana; Vetriani, Costantino; Yücel, Mustafa; Taviani, Marco; Manini, Elena (Frontiers in Microbiology, 2016)
Pockmarks are crater-like depression on the seafloor associated with hydrocarbon ascent through muddy sediments in continental shelves around the world. In this study, we examine the diversity and distribution of benthic microbial communities at shallow-water pockmarks adjacent to the Middle Adriatic Ridge. We integrate microbial diversity data with characterization of local hydrocarbons concentrations and sediment geochemistry. Our results suggest these pockmarks are enriched in sedimentary hydrocarbons, and host a microbial community dominated by Bacteria, even in deeper sediment layers. Pockmark sediments showed higher prokaryotic abundance and biomass than surrounding sediments, potentially due to the increased availability of organic matter and higher concentrations of hydrocarbons linked to pockmark activity. Prokaryotic diversity analyses showed that the microbial communities of these shallow-water pockmarks are unique, and comprised phylotypes associated with the cycling of sulfur and nitrate compounds, as well as numerous know hydrocarbon degraders. Altogether, this study suggests that shallow-water pockmark habitats enhance the diversity of the benthic prokaryotic biosphere by providing specialized environmental niches.